American Capitalism Abroad : Culture and Cash in Billy Wilder's One, Two, Three - Knežević, Borislav (2009)
As the Berlin wall was about to go up in 1961, Billy Wilder was shooting a film called One, Two, Three about a multinational company executive on location in Berlin. The film contains an interesting discourse of commentary on cultural changes in American and global society in the early 1960s, that is, in the middle of the Cold War and at the outset of a new stage in the development of American capitalism, its transnationalization. While hardly a well-crafted work of art, the film’s vigorous engagement with a whole range of contemporary cultural trends is particularly interesting for its perception of an increasing ability of capital to affect cultural production. The essay is designed as a close reading of the film with a focus on its representation of American culture and of emerging transnational capitalism, but it also provides an examination of the generic choices rehearsed by the movie, and in particular, the film’s parody of what Stanley Cavell called the comedy of remarriage.
Projekt MZOS
ENG